Negotiating tradition and modernity: a critical discourse analysis of bride price representations in Chinese newspapers - Liu, Wenyu; Zhang, Siqi; Sun, Chengzhi (Frontiers in Communication, 2025)
IntroductionThis study investigates how Chinese newspapers frame the cultural practice of bride price (caili) and explores how such representations reflect broader socio-cultural tensions between tradition and modernity in contemporary China.MethodsUsing Critical Discourse Analysis (CDA), 113 articles published between 2019 and 2023 are collected from 52 national and local newspapers. The analysis focuses on identifying thematic patterns and discursive strategies.ResultsThe study identifies four dominant themes: (1) high bride price as a socio-economic burden, (2) changing social norms and modernizing marriage practices, (3) governmental interventions and policy reforms, and (4) interplay of gender dynamics. Newspapers predominantly frame high bride prices as detrimental to rural economic development while advocating for “zero bride price” and simplified marriages as markers of modernity and progress. Employing various legitimation strategies, particularly rationalization, moral evaluation, authorization, and mythopoesis, media discourse constructs bride price as a cultural practice requiring reform while acknowledging its traditional significance. Women are portrayed both as commodified objects and strategic agents, revealing ambivalence in gender representation.DiscussionThese competing narratives reflect broader societal negotiations between preserving cultural heritage and embracing modern values in Chinese society. By examining the discursive construction of bride price, this research provides insights into the media's role in shaping cultural practices and contributes to understanding how traditional customs are negotiated within modernizing societies.